Energy price instability and energy efficiency: Korea's macroeconomic framework during the COVID-19 pandemic. - Renhong Wu; Yugang He; Zhuoqi Teng (PLoS ONE)
The pervasive effects of the COVID-19 pandemic in Korea on the daily lives of Korean citizens, as well as the nation's economic and industrial landscape, cannot be understated. In this article, we explore the ramifications of energy price fluctuations, changes in energy efficiency, and shifts in monetary policy on the dynamic macroeconomic framework of the Korean economy during this unprecedented global crisis. Utilizing Bayesian estimation and impulse response functions, the study's findings reveal that a surge in energy prices triggered a cascade of detrimental effects, including reductions in output, investment, employment, energy consumption, real wages, investments, real monetary holdings, and loan interest rates, while simultaneously elevating the deposit interest rate. Conversely, a positive shock to energy utilization efficiency engendered multiple favorable outcomes, such as greater output, consumption, employment, energy consumption, real wages, investment, and real money holdings, along with declines in deposit and loan interest rates. In the short term, a monetary policy shock precipitated an upswing in output, consumption, employment, energy consumption, investment, real money holdings, deposit interest rates, and loan interest rates, while exerting downward pressure on real wages. In sum, integration of these findings into the existing literature on the subject in the Korean context may significantly increase the depth and comprehensiveness of the discourse, improving our understanding of the multiple impacts of the COVID-19 pandemic on the nation's economy.